2019
DOI: 10.24251/hicss.2019.854
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Detection and Characterization of Propaganda Bots

Abstract: Since the revelations of interference in the 2016 US Presidential elections, the UK's Brexit referendum, the Catalan independence vote in 2017 and numerous other major political discussions by malicious online actors and propaganda bots, there has been increasing interest in understanding how to detect and characterize such threats. We focus on some of the recent research in algorithms for detection of propaganda botnets and metrics by which their impact can be measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…BERT (Zellers et al, 2019), RoBERTa and ELMo (Cruz et al, 2019)) have been proposed to handle this fragment-level task. To detect propaganda on social media, many studies (Williamson III and Scrofani, 2019;Caldarelli et al, 2020) utilize datasets that contain propaganda content spread on social media by Russian-based IRA (Farkas and Bastos, 2018;Miller, 2019) or extremists (Johnston and Weiss, 2017;Nizzoli et al, 2019). Subsequent works investigated the influence of propaganda on public opinion (Caldarelli et al, 2020) and the techniques applied to disseminate targeted political agenda (Gorrell et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…BERT (Zellers et al, 2019), RoBERTa and ELMo (Cruz et al, 2019)) have been proposed to handle this fragment-level task. To detect propaganda on social media, many studies (Williamson III and Scrofani, 2019;Caldarelli et al, 2020) utilize datasets that contain propaganda content spread on social media by Russian-based IRA (Farkas and Bastos, 2018;Miller, 2019) or extremists (Johnston and Weiss, 2017;Nizzoli et al, 2019). Subsequent works investigated the influence of propaganda on public opinion (Caldarelli et al, 2020) and the techniques applied to disseminate targeted political agenda (Gorrell et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…Substantial academic effort has been put into the detection of fake accounts (e.g. Davis et al, 2016; Varol et al, 2017; Williamson and Scrofani, 2019) and false information diffusion (e.g. Bastos and Mercea, 2019; Grinberg et al, 2019; Shin et al, 2017; Vosoughi et al, 2018) by analyzing large bodies of digital data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This problem is intensified by evidence that there is a large population of susceptible users on social media who are emotionally charged in their public debates on social media [57] and are unable to distinguish between malicious social bots and other human users. Indeed, studies have shown that social bots have an influence on people by swaying them towards certain positions, creating polarization amongst the public, or obfuscating political issues with tangential information [58].…”
Section: Ojcoms-00446-2021mentioning
confidence: 99%
“…These detection techniques include structurebased systems that explore the networks and interactions of known bots, as bots generally interact with other social bots more than with real accounts to generate their fake social communities. Some of these techniques are available freely to the public through such software as BotOrNot, BotOMeter, and others that provide metrics of bot data and bot scores or the likelihood that an account is a bot [58]; The BotOmeter tests the probability of a Twitter account being a social bot based on multiple features. Some of the features that can be used to detect bots include posting and reposting rates, timing of messages, network patterns (followers and friends), sentiment pattern, etc.…”
Section: V2 Social Media Forensicsmentioning
confidence: 99%
See 1 more Smart Citation